Acetylcholinesterase (AChE) Activity in Embryos of Zebrafish - Gravato, Carlos (2021)
Acetylcholinesterase (AChE) is a useful biomarker for organophosphate and carbamate pesticides exposure. The inhibition of this enzyme has been associated with neurotoxicity and alterations at higher levels of biological organization, such as behavior and development impairments. In this chapter, we describe the methodologies for analyses of AChE activity in pools of 96 h of embryos of zebrafish (Danio rerio) using a spectrophotometric method adapted to 96-well microtiter plates.